2010
DOI: 10.1002/jbm.a.32697
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐free biodegradable scleral plugs providing sustained release of vancomycin, amikacin, and dexamethasone—An in vivo study

Abstract: Delivering effective drugs at sufficiently high concentrations to the area of infection is a standard treatment for infectious disease, such as endophthalmitis. This is currently done by empirical trans pars plana intravitreal injection of both antibiotics directed against gram-positive and gram-negative microorganisms and steroids. However, injections by needles repeatedly may increase the risks of intraocular infection and hemorrhage, as well as retinal detachment. This article explores the alternative of us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…2). The use of biodegradable polymers mixed with vancomycin, amikacin, and dexamethasone as scleral plugs for treatment of endophthalmitis was found to deliver high concentrations of drugs in vivo in experimental endophthalmitis over an extended period of time without any major complications (Peng et al 2010). …”
Section: Anti-inflammatory Therapy: Thecontroversymentioning
confidence: 99%
“…2). The use of biodegradable polymers mixed with vancomycin, amikacin, and dexamethasone as scleral plugs for treatment of endophthalmitis was found to deliver high concentrations of drugs in vivo in experimental endophthalmitis over an extended period of time without any major complications (Peng et al 2010). …”
Section: Anti-inflammatory Therapy: Thecontroversymentioning
confidence: 99%
“…Bacterial invasion of the body causes two pathological processes, which include toxic effects of bacterial virulence factors on the host and host defence [12]. Many studies have shown that bacteria can secrete a variety of toxic substances and that bacterial cell wall components have toxic effects on intraocular tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Elimination of eye tissue damage and improving the final visual outcome in endophthalmitis is challenging. Intravitreal injection of antibiotics is necessary to treat endophthalmitis, and inhibiting the inflammatory response within the eye is also very important [12]. Although the current clinically used antiinflammatory is dexamethasone, controversy remains regarding the use of dexamethasone in experimental models and in clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…They have the theoretical advantage of overcoming medication non-adherence, as well as providing a barrier to prevent microbial seeding while the wound heals. 89 Further research in developing drug delivery systems that are safe and effective can potentially overcome the limitation of patient adherence and further reduce the risk of postoperative endophthalmitis. 83 Small clinical studies suggest that collagen shield use after extracapsular cataract surgery is safe, 84,85 and may reduce the risk of postoperative endophthalmitis in phacoemulsification cataract surgery with clear corneal wounds.…”
Section: Other Therapiesmentioning
confidence: 99%